Assessment of a Reading Comprehension Instrument as It Relates to Cognitive Abilities as Defined by Bloom's Revised Taxonomy - Lorraine Dagostino; James Carifio; Jennifer D. C. Bauer; Qing Zhao; Nor Hashimah Hashim (Current Issues in Education, 2014)
More often than not, the assessment of literacy has focused upon how well readers attain various levels of reading comprehension or demonstrate proficiency with specific reading skills rather than reveal a readers cognitive abilities as reflected in conceptual frameworks such as Blooms Revised Taxonomy (Anderson, et al., 2001). Where tests of reading comprehension have classified test items by type for the purposes of item analysis, it usually is only by reading skill. The focus of this study is to change from this functional approach to one that examines how well, if at all, a test created in Malay, and translated into English, that was developed for primary and intermediate grade readers, may also be able to determine cognitive levels of understanding as described by Blooms Revised Taxonomy The Cognitive Dimension (Hashim et al., 2006). To accomplish this task, the raters evaluated the questions from both Malay tests using Blooms Revised Taxonomy of Cognitive Abilities. By using the Blooms Revised Taxonomy as a system of classification, the researchers were able to more accurately pinpoint the specific cognitive abilities being assessed by each test item. These findings suggested that classification by cognitive level allows one to measure specific cognitive abilities as defined by Blooms Revised Taxonomy. This is significant because Blooms Revised Taxonomy gives us objectives for classifying the learning, teaching and assessing of the cognitive dimension of thought that is central to instruction in most subject areas, and in relationship to our work in reading comprehension as an aspect of assessment of literacy in a way that differs from most current measures of reading comprehension